2017
DOI: 10.1016/j.theriogenology.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Lipid droplets in the ovine uterus during the estrous cycle: Effects of nutrition, arginine, and FSH

Abstract: The aim of this study was to evaluate lipid droplet (LD) expression in uteri of FSH-treated or nontreated sheep administered with arginine (Arg) or vehicle (saline, Sal) and fed a control (C), excess (overfed, O) or restricted (underfed, U) diet. In experiment 1, ewes from each diet were randomly assigned to Arg or Sal treatments administered three times daily starting on Day 0 of the first estrous cycle until blood sample and uterine tissue collection at the early- or mid-luteal phase of the second estrous cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 97 publications
1
2
0
Order By: Relevance
“…Moreover, in the same experiment, administration of 300 μg of 17β-estradiol for 5 d in ovariectomized ewes caused a reduction in the amount of LD, suggesting that high concentration of estradiol during estrus is responsible for the reduced amount of LD observed through metestrus. The accumulation of endometrial LD or total lipids during progression of the estrous cycle from metestrus to diestrus was confirmed by other studies in ewes (Boshier et al, 1987;Meier et al, 1997;Grazul-Bilska et al, 2017) and beef heifers (Wordinger et al, 1977). Consistent among all studies is the location of endometrial LD, which were observed in cells of the luminal and superficial glandular epithelia, and rarely observed in deep glandular epithelium and stroma.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Moreover, in the same experiment, administration of 300 μg of 17β-estradiol for 5 d in ovariectomized ewes caused a reduction in the amount of LD, suggesting that high concentration of estradiol during estrus is responsible for the reduced amount of LD observed through metestrus. The accumulation of endometrial LD or total lipids during progression of the estrous cycle from metestrus to diestrus was confirmed by other studies in ewes (Boshier et al, 1987;Meier et al, 1997;Grazul-Bilska et al, 2017) and beef heifers (Wordinger et al, 1977). Consistent among all studies is the location of endometrial LD, which were observed in cells of the luminal and superficial glandular epithelia, and rarely observed in deep glandular epithelium and stroma.…”
Section: Discussionsupporting
confidence: 77%
“…Histological analysis of LD abundance in endometrial biopsies was performed according to Grazul-Bilska et al (2017). Three 5-μm cross-sections of each biopsy were stained with the green-fluorescence dye boron-dipyrromethene (BODIPY 493/503; 1 μg/mL; Molecular Probes, Eugene, OR) for 20 min, followed by staining of the cells nuclei using the blue-fluorescence dye 4′,6-diamidino-2-phenylindole (DAPI).…”
Section: Endometrial Biopsy Collection Staining and Image Analysismentioning
confidence: 99%
“…As LD accumulation peaks in luteal phase, we assessed a potential hormonal regulation of the lipid processing. Other authors [ 7 , 39 , 49 ] stated that endometrial LD expression might be regulated by steroid hormones and other factors controlling reproductive cyclicity, and regulation of LD formation within the endometrium may be species-specific. However, in our in vitro experiments, stimulation with 17ß-estradiol or progesterone had no significant influence on LD formation and number in canine endometrial epithelial cells.…”
Section: Discussionmentioning
confidence: 99%